STRATEGY DEVELOPMENT OF FOOD SOVEREIGNTY TO ENCOUNTER RADICALISM THREAT IN THE AFGHANISTAN - Arief Rachman; Muhtadi Muhtadi; Kiki Al Hadid (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Higher demand for broader and possible growth of the problem of state instability. Nothing more than a problem triggers social conflict on a small scale to a large scale. This study aims to identify and study various reasons in Afghanistan and also formulate conceptions to increase the responsibility of communities in remote areas. The qualitative method in this study was carried out descriptively based on literature studies. The approach used in this study is integral to the international paradigm and applicable regulations. The results of the study show that the concepts that are following the conditions of the community, increase competitiveness among the environment that can be accessed by the government country in the Afghanistan region and facilitate people to manage the natural resources of the region, conduct and implement site-specific management and develop economic management to produce superior products. Keyword: Food Sovereignty, Radicalism Threat, Afghanistan Region